Evaluating a natural horsemanship program in relation to the ISES first principles of horse training - North, Steve; Hemingway, Ann; McLean, Andrew; Harriet, Laurie; Caroline, Ellis-Hill (2016)
The ISES training principles provide an excellent starting point for professionals and horse owners. Currently, there does not seem to be an accepted protocol for evaluating horse training programs against the ISES principles. We suggest an approach to this, using Parelli Natural Horsemanship as our subject for evaluation. This initial pilot study (single-subject / n=1), trials two analytical methods, as applied to the current, video-based teaching materials from Parelli (latest DVD set, published and commercially available from 2015, supplied by Parelli for use in this study). The two methods used were: (i) ethology-based video observation / logging and (ii) discourse analysis of the language used to teach. The ethology-based approach uses an ethogram, which lists the behavioural characteristics of a human trainer adhering to the ISES principles. Computer-based ‘continuous sampling’ of Parelli video clips was used to log the frequencies of ISES principles. Inter Observer Reliability of the analysis to date was assessed using a two-way, mixed, absolute agreement, average-measures ICC (Intra Class Correlation). This evaluated observer agreement in the frequency count ratings for the ISES principles. Discourse analysis is a qualitative research methodology, applied across many domains including politics and health. Discourse analysis allows us to study transcripts of horse training materials, codifying the words, phrases and linguistic structures. Understanding the context within which training language is used, and its meaning to both the speaker and audience, makes it possible to evaluate compatibility with the ISES principles. Results for the ethology-based observations found all ISES principles present (1-10). High frequency counts for principles 2 & 10. Low counts for principles 5 & 7. Inter Observer Reliability (2 observers) was in the ‘excellent’ range (ICC=0.79). The high ICC value suggests that a minimal amount of measurement error was introduced by the independent observers, and therefore statistical power is not substantially reduced. At this stage (without an ICC value closer to 1.0 or further calibrating observers), increasing the evidence against random effects would require more extensive trials (p=0.16). The interim results from the discourse analysis shows consistent congruence between the Parelli materials and the ISES principles, particularly in the areas of: training according to the horse’s ethology and cognition, using learning theory appropriately, forming consistent habits, avoiding flight responses and ensuring that the horse should always be as calm as possible (1, 2, 7, 9 and 10).